Insight into copper and iron ion sequestration from liquid‑phase environment by microcrystalline cellulose biosorbent: experimental and modelling analyses - Abdullah, Mohammad; Abdullah, Luqman Chuah; Adeyi, Abel Adekanmi; Md Jamil, Siti Nurul Ain; Choong, Thomas Shean Yaw; A. Majid, Rohah (Springer, 2024)
The paper assesses batch system microcrystalline cellulose (MCC) adsorptive ability for copper and iron uptake from aquatic environment. Field emission scanning electron microscope (FESEM), point zero charge and Fourier transform infrared (FTIR) spectroscopy were used to examine the physicochemical and morphological features of MCC. The batch system of the sequestration progression for the elimination of Cu(II) and Fe(II) was used by varying the solution pH, MCC doses, initial copper and iron concentration, and resident time. The maximum removal percentage for Cu(II) and Fe(II) were 99.5% and 96.4%, respectively, at pH 7. The influence of MCC dosage showed the 1.0 g/L of adsorbents results the highest percentage of Cu(II) (99.8%) and Fe(II) (88.63%) correspondingly. Equilibrium data for both metals were well fitted with both Langmuir and Freundlich isotherms, representing monolayer and multilayer adsorption systems. The maximum sorption capacity of MCC was 534.61 mg/g and 845.75 mg/g, respectively, for Cu(II) and Fe(II) ions at room temperature. Pseudosecond-order model best describes the copper and iron kinetic data, signifying the dominance of chemisorption adsorption relation between the negatively charged MCC and adsorbates. After four successive regeneration cycles, the MCC polymer maintained its maximal adsorption capacity, demonstrating effective copper and iron ion separation from aqueous solution. According to the study’s findings, poisonous heavy metals can be successfully removed from aquatic environments using eco-friendly microcrystalline cellulose.